Interfacial adhesion enhanced flexible polycarbonate/carbon nanotubes transparent conductive film for vapor sensing. (October 2019) - Zhou, Bing; Li, Yahong; Zhang, Dianbo; Zheng, Guoqiang; Dai, Kun; Mi, Liwei; Liu, Chuntai; Shen, Changyu
Abstract: Flexible but transparent conductive films (TCFs) have attracted considerable attention recently for their promising applications in flexible electronic devices, sensors and smart window. However, it still remains a great challenge for the facile production of flexible transparent but conductive film with strong interfacial adhesion via a common fabricating strategy. Herein, TCFs based on polycarbonate (PC) film and multi-walled carbon nanotubes (MWNTs) were prepared through an effective R2R spraying technique coupled with hot pressing approach. Interestingly, after hot pressing treatment, the interfacial adhesion between MWNTs and PC has been significantly enhanced without sacrificing transparency and conductivity. Moreover, the film shows good flexibility, without any obvious decrease in performance even upon 1000 bending cycles. Furthermore, PC/MWNTs film after hot pressing exhibits quick response, excellent reversibility and flexibility for volatile organic compounds. The results demonstrate that such TCFs can be used as used as robust sensors with high sensitivity. Highlights: Strong interfacial adhesion between MWNTs and PC was obtained without sacrificing transparency and conductivity. The film shows good flexibility, without any obvious decrease in performance even upon 1000 bending cycles. The film exhibits excellent reversibility flexibility and quick response to volatile organic compounds.